PENGGUNAAN EXCEL DALAM EVALUASI PEMBELAJARAN PAI - Achmad Rasyid Ridha; Salma Navi’ati Kholisa Dewi; Gali Nurma Saudi (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2025)
Learning evaluation is a crucial component of the educational process, including in Islamic Religious Education (PAI). It serves not only to assess the extent of students' achievement of learning objectives but also as a reflective tool for teachers to improve teaching methods, media, and strategies. However, many PAI teachers still face challenges in conducting evaluations manually, such as time-consuming calculations, potential errors, and limited technological proficiency. The use of Microsoft Excel offers an effective and efficient solution for these issues. Equipped with features like automatic formulas, tables, and charts, Excel helps teachers process student scores, analyze learning outcomes, and prepare systematic and accurate reports. Moreover, Excel utilization supports the development of teachers' digital literacy, aligning with 21st-century education demands and the "Merdeka Belajar" (Freedom to Learn) policy. This research employs a library research method to explore the concepts, challenges, and benefits of using Excel in PAI learning evaluation, aiming to provide practical insights for improving the quality and effectiveness of evaluation in schools.